Adsorption of bromate in water using hydrogen peroxide-modified activated carbon - Yongqing Zhang; Yi Qu; Jiali Wang; Deguo Wang (CyTA - Journal of Food)
Activated carbon was modified with 30% hydrogen peroxide. The changes of surface acidic oxygen-containing functional groups before and after modification of activated carbon and the adsorption effect of modified activated carbon on bromate in water were investigated. Activated carbon was characterized by Boehm titration method. The effects of modified activated carbon dosage, adsorption time, pH value and initial bromate concentration in water on bromate removal were observed through static adsorption. The results showed that after modification, the content of total acidic groups, carboxylic group, and phenolic hydroxyl on the surface of activated carbon increased by 40.23%, 98.61% and 146.40%, respectively, and the content of lactone base decreased by 33.29%. Under the conditions of 125 mg modified activated carbon, 2.5 hours of absorption time, pH value of 7.00, and initial concentration of bromate in water of 2.87 mg/L, the removal rate of bromate by modified activated carbon reached the maximum of 98.4%.